National Education Longitudinal Study, 1988: Second Follow-Up (1992) ([Verlag nicht ermittelbar], 1995)
This data collection presents second follow-up data for the NATIONAL EDUCATION LONGITUDINAL STUDY, 1988 (ICPSR 9389). The base-year study, which collected information from student surveys and tests and from surveys of parents, school administrators, and teachers, was designed to provide trend data about critical transitions experienced by students as they leave elementary school and progress through high school and postsecondary institutions or the work force. The first follow-up, NATIONAL EDUCATION LONGITUDINAL STUDY, 1988: FIRST FOLLOW-UP (1990) (ICPSR 9859), provided the first opportunity for longitudinal measurement of the 1988 baseline samples. It also provided a point of comparison with high school sophomores from ten years before, as studied in HIGH SCHOOL AND BEYOND, 1980: A LONGITUDINAL SURVEY OF STUDENTS IN THE UNITED STATES (ICPSR 7896). Further, the study captured the population of early dropouts (those who leave school prior to the end of the tenth grade), while monitoring the transition of the student population into secondary schooling. The second follow-up provides a cumulative measurement of learning in the course of secondary school, and also supplies information that will facilitate investigation of the transition into the labor force and postsecondary education after high school. The 1992 student component collected basic background information about students' school and home environments, participation in classes and extracurricular activities, current jobs, and their goals, aspirations, and opinions about themselves. The student component also gathered data about the family decision-making structure during the critical transition from secondary school to postsecondary education or the work environment. The 1992 school component solicited general descriptive information about the educational setting and environment in which surveyed students were enrolled. These data, which were collected from the chief administrator of each base-year school with sample members still in attendance, cover school, student, and teacher characteristics, school politics and programs, and school governance and climate. The 1992 teacher component was administered to teachers of second follow-up students in one of two basic subject areas: mathematics or science. The questionnaire elicited teacher evaluations of student characteristics and performance in the classroom, curriculum information about the classes taught, teacher demographic and professional characteristics, information about parent-teacher interactions, time spent on various tasks, and perceptions of school climate and culture. The dropout component provides data on the process of dropping out of school as it occurs from eighth grade on. Variables include school attendance, determinants of leaving school, self-perceptions and attitudes, work history, and relationships with school personnel, peers, and family. The parent component provides information about the factors that influence educational attainment and participation, including family background, socioeconomic conditions, and character of the home educational system. This component was present in the base-year survey but not in the first follow-up.